Strategic Information System in Higher Education Institutions: Theoretical model for its design - Gallegos Macías, Marcos Ramón (2025)
Quality management constitutes a fundamental pillar for the responsible fulfillment of the social mission of Higher Education Institutions (HEIs). Therefore, it is essential for these institutions to have valid, reliable, and timely information to support strategic decision-making related to the management of academic processes. The objective of this research was to theoretically and methodologically substantiate a model for the design of Strategic Information Systems at the Universidad San Gregorio de Portoviejo (USGP), located in Manabí, Ecuador. The study followed a descriptive, explanatory, and propositional approach, framed within a non-experimental (cross-sectional) design and a mixed-methods paradigm. Theoretical methods employed included analysis-synthesis, induction-deduction, modeling, and the systemic approach. Among the empirical methods used were document analysis, surveys, interviews, source triangulation, and user consultation. As a result, a theoretical model was developed to guide the design process of a Strategic Information System to support the quality management of academic processes at USGP. The proposed model is structured around a set of interrelated components (essential relationships, objective, principles, approaches, premises, qualities, and stages), which together form a comprehensive, coherent, and applicable conceptual foundation for the design of SIS in HEIs.